2018
DOI: 10.1111/mmi.13933
|View full text |Cite|
|
Sign up to set email alerts
|

Methionine is required for cAMP‐PKA‐mediated morphogenesis and virulence of Candida albicans

Abstract: Candida albicans is a major human fungal pathogen, causing superficial, as well as life-threatening invasive infections. Therefore, it has to adequately sense and respond to the host defense by expressing appropriate virulence attributes. The most important virulence factor of C. albicans is the yeast-to-hyphae morphogenetic switch, which can be induced by numerous environmental cues, including the amino acid methionine. Here, we show an essential role for methionine permease Mup1 in methionine-induced morphog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 87 publications
(106 reference statements)
0
28
0
Order By: Relevance
“…This raises the question about which ligand is able to activate Ca Gpr1. The lab of Van Dijck showed that methionine might be the ligand of Ca Gpr1 as this receptor is required for the methionine-induced and PKA mediated morphogenesis (Maidan et al, 2005a; Schrevens et al, 2018). Furthermore, it was shown that Ca Gpr1 internalizes in the presence of methionine, indicating ligand-induced internalization (Maidan et al, 2005a).…”
Section: Glucose Sensing and Signalingmentioning
confidence: 99%
“…This raises the question about which ligand is able to activate Ca Gpr1. The lab of Van Dijck showed that methionine might be the ligand of Ca Gpr1 as this receptor is required for the methionine-induced and PKA mediated morphogenesis (Maidan et al, 2005a; Schrevens et al, 2018). Furthermore, it was shown that Ca Gpr1 internalizes in the presence of methionine, indicating ligand-induced internalization (Maidan et al, 2005a).…”
Section: Glucose Sensing and Signalingmentioning
confidence: 99%
“…In the past 2 to 3 years, a range of studies have investigated hyphal growth signaling in C. albicans 35 . These studies have made significant advances, in particular in the areas of amino acid inducers of the hyphal transition 36, 37 , gaseous sensing and signaling 3842 , and reactive oxygen and oxidative stress signaling 4345 . Extensive analyses of filamentation programs revealed media-independent genetic requirements for filamentation, in particular RIM101 (pH-dependent pathway) and GPA2 (Gα functioning in the cAMP/PKA pathway), in addition to a core transcriptional profile 46 .…”
Section: Hyphal Growth Signalingmentioning
confidence: 99%
“…Inhibition of mitochondrial activity resulted in reduced Ras1 and Cyr1 activity and consequently attenuated filamentation [ 89 ]. In addition, other proteins, such as Hsp90 and its co-activator Sgt1, regulate morphogenesis and drug tolerance in C. albicans [ 30 , 90 ], and small chemical compounds have also been found to control its morphogenesis via the cAMP/PKA pathway [ 91 , 92 , 93 ]. Furthermore, as the cAMP/PKA pathway is conserved in eukaryotic cells and regulates virulence in C. albicans and C. tropicalis , this pathway might be a promising target for antifungal drug development.…”
Section: Discussionmentioning
confidence: 99%